The Potential of Private Health Insurance Ownership Based on the 2018-2020 National Socioeconomic Survey Data - Hasan, Arief Rosyid; Bachtiar, Adang; Candi, Cicilya (UI Scholars Hub, 2022)
In 2014, the Indonesian Government introduced a social security program in the health sector. However, Indonesia’s out-of-pocket expenses remain high due to a lack of public interest in National Health Insurance services. Financing expensive health services with high out-of-pocket expenses has the potential to cause poverty. Private health insurance is considered a solution to this problem. This study aimed to determine the socioeconomic factors of private health insurance ownership and its potential in Indonesia. This study used secondary data from the 2018, 2019, and 2020 National Socioeconomic Surveys. Logistic regression analysis showed that the variables related to private health insurance ownership were age, sex, education, economic status, employment status, marital status, household status, and location of residence. The most dominant variable in 2018 was per capita expenditure (economic status), while education was the most dominant variable in 2019 and 2020. The result of this study can be used to formulate a strategy for increasing participation in private health insurance. The socioeconomic health sector should use this information to target specific markets for private health insurance.